Transdisciplinary Approach to Training Future Managers for Digital Education in Yakutia - Barakhsanova, Elizaveta Afanasyevna (2020)
The article discusses the effectiveness of a transdisciplinary approach to training future managers of Yakut education. The study is based on the analysis of Russian and foreign theoretical positions on education management and organization of teaching programs for future education managers in the context of the digital education implementation. The authors examined the experience of managing and organizing the educational process at the North-Eastern Federal University (NEFU), Churapchinsky State Institute of Physical Culture and Sports (CSIPCS), and Yakut State Agricultural Academy (YSAA). One of the research methods was a survey of 250 students of these institutes, who are completing their Master’s program in the following courses: Project Management in Education (NEFU), Innovation Processes in Education (NEFU), Corporate Digital Training (NEFU), Digital Training Management and Technology (NEFU), Vocational Education and Management in the Field of Physical Culture and Sports (CSIPCS), Management of the Crops Production Process in the Permafrost Zone (YSAA). The results of the study revealed the main features and trends of the educational management in a university. Practical significance of the work lies in the study and development of experience in introducing a transdisciplinary approach to training future managers of education.